Nepal Jobs Diagnostic - Ruppert Bulmer, Elizabeth (World Bank, Washington, DC, 2020)
Nepal’s economy is gradually shifting from largely subsistence agriculture to more modern industry and services. Agriculture’s share of domestic output and employment is declining, industry is holding steady and services now account for over half of total domestic production. In the last two decades, large numbers of men have entered jobs in construction, manufacturing, commerce and transportation, among others; even though most of these are informal jobs1 or temporary wage jobs, they are nevertheless more productive and provide improved livelihoods compared to traditional low-productivity farm work. Women, on the other hand, have not transitioned in significant numbers. Nepal’s structural transformation has been slow due to the prevalence of subsistence activities. Nepal remains a largely agrarian economy characterized by small-scale family farming using traditional methods and producing primarily for household consumption. Six in 10 workers are engaged in agriculture but generate only one-third of total output (Figures 0.1a and 0.1b). Over half of the labor force does not produce enough output on their farms or in their households to generate surplus to sell in the market. The policy interventions to improve job outcomes in Nepal presented here are considered through four main channels: (a) fostering SME productivity and growth; (b) improving the business environment and labor market policies; (c) increasing the individual, family and economy-wide benefits of international migration; and (d) preparing and connecting women and youth to better job options including entrepreneurship. Firms of all sizes need to become more competitive to expand production and create more jobs, including better quality jobs requiring higher skills. Entrepreneurs (including the self-employed) need to differentiate their products and services and identify new markets. This includes rural producers, especially women. Updating methods to increase yields and product quality and integrating into value-chains would raise rural productivity and earnings. To grow, SMEs need policies to facilitate access to finance and business knowledge, reduce regulatory and tax burdens, and improve market connectivity. Increasing the returns to migration—for both the migrant worker and the sending family, will boost job quality and household earnings, with positive economic spillovers. Expanding women and youth access to better jobs in a wider range of activities, and ensuring they have the necessary skills to succeed, will accelerate structural transformation and boost labor earnings. Strengthening guidance for schoolchildren and out-of-school youth to prepare them for the labor market will increase the relevance of their skills. And expanding access to assets, services, know-how and networks for informal producers and entrepreneurs in both urban and rural markets will enhance productivity and living standards.